Leg and calf press training modes and their impact on jump performance adaptations - Caruso, J. F.; Coday, M. A.; Ramsey, C.; Griswold, S. H.; Polanski, D. W.; Drummond, J. L.; Walker, R. H. (The Journal of Strength and Conditioning Research, 2008)
To examine the effects of resistance exercise (REX) mode on jump performance, subjects were assigned to one of three groups over a 6-week period with no cross-over. Subjects were assigned to leg and calf press REX on either a standard (n = 10) or ergometer (n = 9) device while a third group (n = 9) served as controls (CTRL). REX subjects worked out twice per week, which consisted of a three-set, 10-repetition paradigm for leg and calf press exercises. Immediately before and after the 6-week period, subjects performed tests that assessed jump (standing vertical jump, four-jump test protocol, depth jump) ability, while a fourth estimated knee extensor fast-twitch percentage (FT%) from fatigue incurred through a 50-repetition isokinetic protocol. Data analyses utilized 3 x 2 (group x time) repeated-measures ANCOVAs. Several dependent variables showed effects by group (standard REX, ergometer REX > CTRL) and time (post > pre). An interaction occurred for explosive leg power factor, a four-jump test variable, with standard REX post-test values as the interaction source. A trend for an interaction occurred for depth jump hang time, as ergometer REX values improved over time. Results suggest that mode-specific adaptations occur with REX training. Thus, athletes are best served with the selection of a REX device that is most specific to the demands of their jump performance task.